Comparative maxicircle analysis in Trypanosoma species from the LSRM clade highlights patterns in an underexplored lineage - Fanny Rusman; Valeria Aramayo; Noelia Floridia-Yapur; Anahí Guadalupe Díaz; Tatiana Ponce; Soledad Hodi; Juan José Aguirre; Gonzalo Greif; Luisa Berná; Carlos Robello; Patricio Diosque; Nicolás Tomasini (PLoS ONE, 2025)
Trypanosoma lainsoni, Trypanosoma platydactyli, and Trypanosoma scelopori are kinetoplastid flagellates belonging to the LSRM clade of the genus Trypanosoma. These parasites have a unique mitochondrial DNA structure, the kinetoplast, comprising catenated maxicircles and minicircles. However, genetic information on the kinetoplasts of these species remains unknown. In this study, we assembled and analyzed maxicircles from different isolates of T. lainsoni, T. platydactyli, and T. scelopori to address the current gap in genetic information about the LSRM clade and explore their phylogenetic relationships within the Trypanosoma genus. The maxicircle of T. lainsoni isolate Le29, including the coding and divergent regions, was de novo assembled combining Illumina and Oxford Nanopore Technologies, revealing a length of 49,306 bp. Additional isolates of T. lainsoni (Ca37 and Ca47), as well as T. platydactyli and T. scelopori, were sequenced with Illumina, yielding complete coding regions and partial divergent regions for all. As in other trypanosomes, coding regions exhibited conserved synteny in gene order and RNA editing patterns. We found that mRNA editing by U-insertion was higher in T. lainsoni than in T. cruzi, suggesting a partial loss of editing in the latter. Phylogenetic analyses based on the coding region positioned the LSRM clade alongside the Aquatic clade as one of the most ancestral groups within non-salivarian trypanosomes and supported the ancestral position of the Trypanosoma brucei clade, contrasting with previous reports. Finally, analysis of the maxicircle divergent region suggests a gradual transition from long to short repeat structures in non-salivarian trypanosomes. This study provides the first characterization of the T. lainsoni maxicircle and related LSRM clade species. These findings provide new insights into the ancestral relationships within the group, the evolution of the divergent region of the maxicircles and propose RNA editing has been evolving within the genus.